A gyroidal pyramid searching model in digital ecosystems - Zhu, Dengya; Dreher, Heinz (Institute of Electrical and Electronics Engineers (IEEE) Industrial Electronics Society, 2009)
When ambiguous search terms are submitted to search engines, search results are usually literally but not always semantically relevant to the search terms. Users need to manually pickup relevant results from among thousands of the hit-list items. A gyroidal pyramid information retrieval model is proposed which intends to refine the results by grouping them into a predefined Web ontology, lets users choose which category is of interest, and thus presents the users with refined results. Users are allowed to choose subcategory to further re-fine the results, or choose another interesting category. Pre-liminary experimental results are positive and encouraging.